An Andean Avatar : Post-neoliberal and neoliberal strategies for promoting extractive industries /: Post-neoliberal and neoliberal strategies for promoting extractive industries. (April 2010) - Bebbington, Anthony, 1962-; Bebbington, Denise Humphreys
No abstract available